2016
DOI: 10.1002/lary.26455
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of surgically treated human papillomavirus–related oropharyngeal squamous cell carcinoma with N3 disease

Abstract: 4. Laryngoscope, 127:2033-2037, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…This study represents one of the very few studies of patients with p16‐positive N3 OPSCC . In our series, patients had a 5‐year OS of 67.5%, so relatively good outcomes as compared to previously published survival of patients with a p16‐negative N3 disease (Table ).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…This study represents one of the very few studies of patients with p16‐positive N3 OPSCC . In our series, patients had a 5‐year OS of 67.5%, so relatively good outcomes as compared to previously published survival of patients with a p16‐negative N3 disease (Table ).…”
Section: Discussionsupporting
confidence: 53%
“…However, the rates of oropharyngeal localizations among series of N3 have been ranging from 13% for Chan et al, to 76% for Adams et al, depending on the country and the date . Results from more recent studies are somehow very divergent regarding treatment outcomes specifically in OPSCC . The obvious reason for this shift of prognostic is the worldwide increasing incidence of papillomavirus‐associated p16‐positive OPSCC, which present more often with an advanced lymph node staging but yield better survival rates as compared to tobacco‐ and alcohol‐induced disease .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Several studies 6,8 have reported that the previous edition of the AJCC staging manual (AJCC-7) could not reliably fulfill the prognostic needs of HPV-positive patients. Additional studies 8,27 about HPV-positive patients with OPSCC found that the AJCC-7 pT stage was significantly associated with survival, but the nN stage was not. A recent study 27 from the Washington University School of Medicine found that pN3 cases were equivalent to N1 cases and pN1 was associated with better survival than pN0.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in a recent multivariable analysis investigating prognostic factors in patients with HPV‐related oropharyngeal SCC after definitive chemoradiation, N3 classification was the single most significant risk factor for locoregional failure . In a recent review of patients with N3 neck disease from HPV‐related oropharyngeal SCC managed with primary surgery and adjuvant therapy, however, the regional recurrence rate was only 5% . Nonetheless, the resectability of the nonsurgical cases is uncertain and comparisons are confounded by unknown variables.…”
Section: Discussionmentioning
confidence: 99%